(untitled) ("Conference on Universal Science Research 2023", 2024)
We know that a preschooler is the age when he can use the basic skills of literacy in his daily activities. Therefore, in order to teach the child literacy skills, to attract him, it is necessary to consciously conduct literacy activities every day. Because the more a child meets letters and written words, the stronger his language skills will be. This article talks about different ways to help preschoolers develop their literacy skills.